2019
DOI: 10.3758/s13414-019-01681-z
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty as a determinant of attentional control settings

Abstract: Previous studies have demonstrated that attentional capture occurs based on attentional control settings. These settings specify what features are selected for processing as well as what features are filtered out. To examine how attentional control settings are flexibly constructed when target and/or distractor features are uncertain, the current paper presents four experiments in which the numbers of target and distractor features were manipulated. The results showed that attentional control settings were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We refer to differences between invalid and valid cue trials (invalid -valid) as cueing effects. The prototypical result of contingent capture is that cueing effects with cues matching the target are larger than cueing effects with cues that do not contain any target features (e.g., Becker et al, 2019;Burnham, 2019;Jung et al, 2021;Kim et al, 2019;Ruthruff et al, 2020;Schönhammer et al, 2020). Therefore, the difference between matching and nonmatching cues indicates that an attentional template for the target color was established.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to differences between invalid and valid cue trials (invalid -valid) as cueing effects. The prototypical result of contingent capture is that cueing effects with cues matching the target are larger than cueing effects with cues that do not contain any target features (e.g., Becker et al, 2019;Burnham, 2019;Jung et al, 2021;Kim et al, 2019;Ruthruff et al, 2020;Schönhammer et al, 2020). Therefore, the difference between matching and nonmatching cues indicates that an attentional template for the target color was established.…”
Section: Introductionmentioning
confidence: 99%
“…The result was that spatial cues in the targetmatching color captured attention, whereas spatial cues in the nonmatching color did not. Thus, the difference between target-matching and nonmatching spatial cues shows that an attentional template was activated for the target color, but not for an unrelated color (e.g., Becker et al, 2019;Burnham, 2020;Jung et al, 2021;Kerzel, 2019;Kim et al, 2019;Ruthruff et al, 2020;Schönhammer et al, 2020). Attentional capture is measured as the difference in RTs between spatial cues appearing at the target location (valid cues) and spatial cues appearing at a nontarget location (invalid cues).…”
mentioning
confidence: 99%
“…In dual target search, two features are relevant, whereas only a single feature was relevant in the present study. For instance, numerous studies have shown that participants can establish attentional templates for two colors (Ansorge et al, 2005; Beck et al, 2012; Berggren et al, 2020; Grubert & Eimer, 2015, 2016; Huynh Cong & Kerzel, 2020; Kerzel & Witzel, 2019; Kim et al, 2019; Moore & Weissman, 2010; Roper & Vecera, 2012). In these studies, the colors were presented on separate objects to establish two attentional templates.…”
Section: Discussionmentioning
confidence: 99%